PENGUJIAN XRF DAN XRD UNTUK IDENTIFIKASI KANDUNGAN MINERAL PASIR DI PANTAI TALANG SIRING - Ariyanto, Sandy Vikki; Joni, Idon; Yunanto, Fredy (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2023)
In the Talang siring tour of the Pamekasan district, numerous illegal mining operations along the coast for sale and personal use produce building materials with low economic value. However, if the sand is processed further, it will produce materials with high technology utilization and economic value. This research is a preliminary investigation into converting sand into high-value minerals to be utilized economically. Using X-Ray Fluorescence (XRF) and X-Ray Diffraction (XRD) experiments, this study aims to determine the sand's mineral content in the Talang Siring tourist area in Pamekasan Regency. Initial identification is the XRF test function for analyzing sand's chemical elements and composition. The purpose of XRD is to analyze the crystal structure and correlate the results with Macth and origin software based on the XRF results. The results of the XRF test indicated that Silicone had the highest concentration of minerals at 63.8%, followed by Calcium at 29.4% and Iron at 2.45%. The XRD test results indicated that the sand's mineral composition was qualitatively SiO2 90%, CaCO3 8%, Iron 1%, and the remainder 1%.